Heterogeneous Catalysis with Basic Compounds to Achieve the Synthesis and C–N Cleavage of Azetidin-2-ones under Microwave Irradiation - Galván, Adriana; de la Cruz, Fabiola N.; Cruz, Francisco; Martínez, Merced; Gomez, Clarisa Villegas; Alcaraz, Yolanda; Domínguez, José Manuel; Delgado, Francisco; Vázquez, Miguel A. (Synthesis, 2019)
The synthesis of azetidin-2-ones with a completely heterogeneous catalysis is reported. The use of basic compounds as solid catalysts allowed for the synthesis of azetidin-2-ones under microwave irradiation without organic additives such as triethylamine. An excellent catalyst for this transformation was Mg-Al hydroxide (MAH). The present methodology offers the advantages of non-hazardous reaction conditions, short reaction times, high yields, and catalyst reusability. Different substitution groups were tested on the imines and acyl chlorides to explore the scope of the reaction. Unconventional N–C4 bond cleavage was detected in azetidin-2-ones. MAH was characterized by N2 adsorption–desorption, X-ray diffraction (XRD), scanning electron microscopy (SEM), and high-resolution transmission electron microscopy (HR-TEM).
Keywords: heterogeneous catalyst; Mg-Al hydroxide; azetidin-2-ones; ring opening; microwave irradiation